Marketing Mix and Green Marketing Effects on MSME Customer Loyalty through Value and Satisfaction - Galih Raspati; Yuyun Yuniati Yuningsih; Afrizal Maulana; Mulfi Sandi Yuda; Yoki Muchsam (International Journal of Multidisciplinary Sciences and Arts, 2026)
The rapid growth of healthy food micro, small, and medium enterprises (MSMEs) in Indonesia is driven by increasing consumer awareness of health and environmental sustainability. Nevertheless, intense competition and low switching costs pose challenges for MSMEs in sustaining long-term customer loyalty. This study aims to examine the effects of the marketing mix (7P) and green marketing on customer loyalty, with perceived value and customer satisfaction as mediating variables. A quantitative research design with a cross-sectional survey approach was employed. Data were collected from customers of healthy food MSMEs in Bekasi using structured questionnaires. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to assess both direct and indirect relationships among variables. The results indicate that the marketing mix (7P) and green marketing have significant positive effects on perceived value, customer satisfaction, and customer loyalty. Perceived value and customer satisfaction also significantly influence customer loyalty and partially mediate the relationships between marketing mix, green marketing, and loyalty. These findings suggest that integrating conventional marketing strategies with sustainability-oriented practices is essential for enhancing customer loyalty in healthy food MSMEs. This study contributes to the literature by proposing an integrated model that combines marketing mix and green marketing in explaining customer loyalty, particularly within a developing-country and peri-urban context. Practically, the findings highlight the importance of improving service quality, pricing transparency, and credible green practices to strengthen competitiveness and customer retention.